Early humans - Merriman, Nick; Wilkinson, Philip; Davenport, Vicky; King, Dave; Art Ed. (New York Alfred A. Knopf, 1989)
Text and photographs present a description of early humans: their origins; their tools and weapons; how they hunted and foraged for food; and the role of family life, money, religion, and magic.
Man or ape? -- Prehistoric food -- The toolmakers -- Flintworking -- Moving northwards -- The coming of fire -- Life in the Ice Age -- Ice Age hunters -- Modern humans -- The first artists -- Hunting and gathering -- Hunters of the desert -- Tilling the soil -- Clothing and fabrics -- Skin deep -- Magic -- Death and burial -- Ancient writing -- Bronzeworking -- The beauties of bronze -- A Bronze Age warrior -- Iron Age finery -- Life in the Iron Age -- Men of iron -- Ancient China -- Small change -- Central Americans -- North Americans -- Digging up the past.
Includes index.
Keywords: Prehistoric peoples -- Juvenile literature; Civilization, Ancient -- Juvenile literature; Prehistoric peoples; Civilization, Ancient